Respiratory Muscles Training in the Complex Treatment of Patients with Acute Decompensated Heart Failure - N. T. Vatutin; A. N. Shevelyok; E. V. Sklyannaya; I. G. Linnik; A. V. Kharchenko (SINAPS LLC, 2022)
The aim: to evaluate the efficacy of respiratory muscles training in the complex treatment of patients with acute decompensated heart failure. Material and methods. A prospective randomized study included 120 patients (71 men and 49 women, mean age 73,6±5,8 years) hospitalized with acute decompensated heart failure. The main exclusion criteria were: requirement for treatment in intensive care unit; hemodynamic instability; severe pulmonary and other concomitant pathology. After initial procedures all patients were randomized to breathing exercises performed in addition to standard therapy (main group, n=60) or to standard therapy only (control group, n=60). Patients of the main group were trained in the technique of complete yogic breathing, which consists of three successive phases: abdominal, thoracic and clavicular. The participants practiced full breathing daily at least 3 times a day for 10 minutes under the supervision of instructor. The primary endpoint of the study was the change in dyspnea according to the modified Borg scale (modified by V.Yu. Mareev) on the 7th day of treatment. Results. During treatment the severity of dyspnea decreased in both groups, more significantly in the main group (from 6 (5; 6) to 3 (2; 3) points) compared to control (from 6 (5; 6) to 4 (3; 4) points, p <0,05). Significant differences between the groups were also obtained for the secondary variables of efficacy: six-minute walk distance, heart rate and breathing rate at rest, blood oxygen saturation (p ><0,05). In patients who performed breathing exercises, body weight decreased faster (0,72±0,06 kg/day versus 0,53±0,06 kg/day, p ><0,001), although the volumes of excreted fluid did not differ between the groups. In the main group moist rales in the lungs were stopped by the sixth day of hospitalization (interquartile range of 5-7 days), and in the control group - by the eighth (interquartile range of 7-9 days), p=0,024. The duration of active diuretic phase and the average daily doses of diuretics were lower in main group compared to control (p ><0,05). During hospitalization quality of life improved in both groups, more significantly in respiratory muscles training group (p ><0,01). In-hospital mortality and the rate of transfers to the intensive care unit did not differ between groups. The average hospital stay in surviving patients was significantly shorter in main group than in control (14,2±2,5 versus 17,3±2,9 days, p ><0,001). >Conclusion. Respiratory muscles training with full yogic breathing in addition to standard medical therapy for patients with acute decompensated heart failure leads to a more significant reduction in the severity dyspnea, increased exercise tolerance, improved blood oxygen saturation, and reduced need for diuretics. The use of full breathing is associated with significant improvement in the quality of life and decrease in the length of hospital stay, but does not lead to improvement in hospital outcomes.